Metode Dan Pendekatan Dalam Kajian Islam - Fauzi Ahmad Syawaluddin; Afifah Siregar; Erlina Wati Dongoran; Nur Aisya Nasution; Pintar Rokaya Siaahan (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
Islamic studies is one of the studies that has received attention from various scientists. If examined carefully, it appears that Islamic studies have begun to be widely discussed by those who are interested in religious studies and other studies. In this way, Islamic studies deserves to be one of the favorite branches of science. It can be interpreted that the study of Islamic studies already has a position in the world of science. The approach is one of the viewpoints and paradigms used by researchers in analyzing an Islamic religious object using existing religious knowledge and theories. Existing knowledge or theories are basically used as analytical tools or tools based on problems related to religion so that the object and environment of study are clearly visible